Writing for the Medium Television in transition - Elsaesser, Thomas (Film Culture in Transition, 1994)
This collection of essays, by well known writers on the subject of writing for television, is divided into three sections, with the first one devoted to the debates on quality television. The second one focuses on literature and television. The final section examines 'Science on television', with series editors from Britain and Germany giving first-hand accounts of the scope for serious science reporting on television.